Building Brands Together: Emergence and Outcomes of Co-Creation. (May 2013) - Ind, Nicholas; Iglesias, Oriol; Schultz, Majken
Co-creation is a rapidly emerging area of research. However, there is a lack of understanding as to how organizations use co-creation to build relationships and generate value. How does participation emerge and what outcomes does it deliver? To generate insight into the co-creation process, we created an online brand community. Our findings show that people participate in a community because it offers them the chance to find fulfillment, to express their creativity, and to socialize. The findings have significant implications for marketing, branding, and research professionals because the research shows that managers have to see participants as integral to the brand.